2014
DOI: 10.1080/17429145.2014.983568
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of abiotic salt stress inOchradenus baccatus(Del.) byTrichoderma hamatum(Bonord.) Bainier

Abstract: The current study was taken up to examine the role of bioagent (Trichoderma hamatum) in mitigating the deleterious effects of NaCl stress in Ochradenus baccatus. Varying concentrations of salt (0, 75, and 150 mM) were used to observe the effect on growth, pigments, some key metabolic attributes, antioxidant enzymes, and elemental accumulation in O. baccatus. The results indicated significant decrease in seed germination, plant growth, pigment content, membrane stability index, tissue water content, and total l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 57 publications
(59 reference statements)
10
32
0
Order By: Relevance
“…Activity of APX and GR were further increased by AMF and thus reducing oxidative stress effects of salinity. An increase in activity of antioxidants is often correlated with the enhanced tolerance of plants to stress (Ahmad, 2010;Hashem et al, 2014b). AMF induced significant increase in activity of APX under normal and salt stress in the present study is in concurrence with the results of Abdel Latef and Chaoxing (2011) and .…”
Section: Membrane Stability Index and Malonaldehyde (Mda)supporting
confidence: 81%
See 4 more Smart Citations
“…Activity of APX and GR were further increased by AMF and thus reducing oxidative stress effects of salinity. An increase in activity of antioxidants is often correlated with the enhanced tolerance of plants to stress (Ahmad, 2010;Hashem et al, 2014b). AMF induced significant increase in activity of APX under normal and salt stress in the present study is in concurrence with the results of Abdel Latef and Chaoxing (2011) and .…”
Section: Membrane Stability Index and Malonaldehyde (Mda)supporting
confidence: 81%
“…Exposure to stress triggers accumulation of proline in plants. The increase in proline content under present study is in corroboration with Ahmad (2010), Alqarawi et al, (2014a) and Hashem et al, (2014b). Harinasut et al (2000) reported manifold increase in proline accumulation in Morus alba plants subjected to salt stress.…”
Section: Membrane Stability Index and Malonaldehyde (Mda)supporting
confidence: 78%
See 3 more Smart Citations